2018
DOI: 10.1021/acs.jmedchem.7b01417
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of Orally Bioavailable Quinoline–Indole Derivatives as Innovative Multitarget-Directed Ligands: Promotion of Cell Proliferation in the Adult Murine Hippocampus for the Treatment of Alzheimer’s Disease

Abstract: A novel series of quinoline-indole derivatives were synthesized and evaluated as multitarget-directed ligands for the treatment of Alzheimer's disease (AD). Biological evaluation revealed that the derivatives had multifunctional profiles including antioxidant effects, blood-brain barrier (BBB) penetration, biometal chelation, Aβ aggregation modulation, neurotrophic and neuroprotective properties. Moreover, several representative target derivatives demonstrated hippocampal cell proliferation in living adult mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 48 publications
0
46
0
Order By: Relevance
“…WI-1758 is also able to chelate Cu 2+ , Zn 2+ , Fe 2+ , and Fe 3+ . WI-1758 hydrochloride has a good pharmacokinetic profile with an oral bioavailability of 14.1% and the ability to permeate BBB in vivo (LogBB value of −0.19), besides its chronic oral administration ameliorated deficits in APP/PS1 AD mice and reduced Aβ deposits [33]. Another recent approach aimed to combine the antioxidant and neuroprotective properties of (R)-alpha-lipoic acid (LA) and the chelating capacity of 8-HQ, resulting in a novel multitarget ligand (5a, in Figure 5), with antioxidant, chelating and neuroprotective properties for the treatment of neurodegenerative disorders, such as AD and PD [34].…”
Section: Treatment Of Alzheimer's Diseasementioning
confidence: 99%
“…WI-1758 is also able to chelate Cu 2+ , Zn 2+ , Fe 2+ , and Fe 3+ . WI-1758 hydrochloride has a good pharmacokinetic profile with an oral bioavailability of 14.1% and the ability to permeate BBB in vivo (LogBB value of −0.19), besides its chronic oral administration ameliorated deficits in APP/PS1 AD mice and reduced Aβ deposits [33]. Another recent approach aimed to combine the antioxidant and neuroprotective properties of (R)-alpha-lipoic acid (LA) and the chelating capacity of 8-HQ, resulting in a novel multitarget ligand (5a, in Figure 5), with antioxidant, chelating and neuroprotective properties for the treatment of neurodegenerative disorders, such as AD and PD [34].…”
Section: Treatment Of Alzheimer's Diseasementioning
confidence: 99%
“…An earlier paper by Wang et al (2018) described the synthesis of new 8-hydroxyquinoline derivatives, as shown in Figure 6 [ 61 ]. Compounds 88 and 89 were prepared from 8-HQ by reaction first with formaldehyde in the presence of hydrogen chloride, followed by reaction with triethylphosphite to afford diethyl ((8-hydroxyquinolin-5-yl)methyl)phosphonate [ 56 ].…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…A very detailed research involving several quinoline-indole-based derivatives pointed out the ability of these compounds in promoting cell proliferation in the adult murine hippocampus, as a result of their neuroprotective effect against A β -related toxicity and oxidative stress [ 138 ]. Although there would be more than one analogue that may be worthy of investigation, the optimized compound 59 ( Figure 17 ) has been identified as the most promising candidate of the series and arose from the combination of the Clioquinol structure with the substituted indole fragment.…”
Section: Target Combinations In Mtdl Design Strategy For Admentioning
confidence: 99%